Encapsulation of genistein in glycidylated G3 polyamidoamine dendrimers enables diffusion of genistein through biological membranes and anti-nematode activity of the encapsulate - Filipowicz-Rachwał, Aleksandra; Drozdowska, Joanna; Zagórska-Dziok, Martyna; Uram, Łukasz; Wołowiec, Stanisław (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Poorly soluble isoflavonoid genistein is known as an anti-nematode agent and also it decreases the risk of certain types of cancer. The biological activity of genistein is limited mostly by its low solubility. Therefore many attempts to increase genistein solubility in water were reported. We applied a polyamidoamine dendrimer, modified its surface by glycidylation, and used this macromolecule as a guest for genistein. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Polyamidoamine dendrimer 3rd generation was substituted with 64 glycidol residues to obtain a macromolecule host for genistein. The stoichiometry of this host-guest complex was determined. The complex was tested for skin model permeability, toxicity on fibroblast (BJ) and keratinocyte (HaCaT) cell lines in vitro and anthelmintic activity on the Caenorhabditis elegans nematode. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The partition coefficient of genistein between octanol and water was determined (KO/W). The 1:1 host-guest complex was isolated and used as drug delivery system for genistein delivery. PAMAM G3 glycidyled dendrimer containing genistein indicated an anthelmintic activity at 50 µM concentration. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The solubility of genistein in water increases 640 times in presence of an equimolar concentration of the dendrimer. One molecule of host dendrimer encapsulates 3 molecules of genistein. The encapsulate is an efficient anti-nematode formulation.